Isolated Terminal Ileal Mucosal Changes: When is the Bite Indicated? - Jain, Mayank; Srinivas, M.; Ravi, R.; Mahadevan, B.; Michael, Tom; Venkataraman, Jayanthi (Journal of Digestive Endoscopy, 2018)
Aim: This study aims to determine the clinical presentation, and ileal mucosal changes during colonoscopy for which terminal ileal (TI) biopsies were taken at our center and to determine the specific histopathology which had the best yield for specific colonoscopy findings. Materials and Methods: Retrospective audit of all patients who underwent colonoscopy with ileoscopy between 2012 and 2016. All patients with TI mucosal changes and normal colonic mucosa, who underwent ileal biopsy, were included in this study. Patient data regarding age, gender, indication for ileocolonoscopy (screening for colorectal cancers, inflammatory bowel disease [IBD], or irritable bowel syndrome [IBS]) and histopathology changes were collected. Appropriate statistical tests were used and P < 0.05 was considered statistically significant. Results: One hundred and nine patients had isolated ileal lesions. The median age was 44.1 years (range 8–80 years). Men outnumbered women in a ratio of 82:27. The major clinical indications for ileocolonoscopy were IBS (64.2%), followed by IBD (22%). Ulcers (aphthoid) were the most frequent finding followed by mucosal nodularity and nonspecific findings. Ulcers in ileum were most often reported as chronic ileitis (46.2%), followed by nonspecific changes (35.2%) Biopsy from nodular ileal lesions, were predominantly nonspecific (74.4%), followed by acute (15.4%) and chronic ileitis (10.2%). About 50% of specimens with nonspecific ileal changes had nonspecific histological changes. Ileal ulcers had the highest sensitivity, PPV, and NPV for significant histological findings. Conclusion: Ileal ulcers are the significant colonoscopy findings where tissue biopsy is likely to yield a definitive diagnosis and justify specific management. Biopsies from nonspecific ileal changes and nodularity should be discouraged as it is unlikely to pick up any major abnormality.
Keywords: Biopsy; ileum; intestine